The effect of zinc and copper proteinate on the growth and development of crossbred pigs during fattening - V. S. Bomko; S. G. Karapysh; Yu. G. Kropyvka (Науковий вісник Львівського національного університету ветеринарної медицини та біотехнологій імені С.З. Гжицького. Серія: Сільськогосподарські науки)
The article presents the results of a scientific and production experiment studying the impact of different levels of zinc and copper proteinate in the diets of fattening pigs, as well as the feed efficiency for one kilogram of live weight gain. The inclusion of zinc and copper proteinate in the compound feeds for four breeds of fattening piglets led to an increase in the average daily gain and a reduction in feed costs per unit of production compared to animals that received zinc and copper sulfates. The best results for growth intensity and feed conversion efficiency were recorded in pigs of the 4th experimental group, which received compound feeds containing zinc proteinate (166.4 g/ton) and copper proteinate (5.45 g/ton). The study confirms the importance of balanced feeding for achieving high productivity in hybrid pigs, particularly in providing essential trace elements such as zinc and copper. These elements are crucial for various biological processes, including enzymatic activity, metabolic regulation, and immune system function. The use of organic trace elements, such as chelated complexes, enhances the absorption and bioavailability of these substances compared to inorganic salts like sulfates. The results of the study show that the inclusion of zinc and copper proteinate in pig diets significantly improves their performance during fattening, increasing both growth intensity and feed efficiency. The use of chelated forms of trace elements in pig feeding allows for better results, reduces feed costs, and ensures high profitability in pork production. The research also highlights the need for continuous optimization of compound feed formulations to create optimal conditions for the growth and development of pigs, which is essential for modern pig farming. In particular, it emphasizes the importance of scientific research and the implementation of innovative approaches to animal feeding to achieve high results in meat production.